2019
DOI: 10.1002/slct.201902648
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐(phenoxyalkyl)‐, N‐{2‐[2‐(phenoxy)ethoxy]ethyl}‐ or N‐(phenoxyacetyl)piperazine Derivatives and Their Activity Within the Central Nervous System

Abstract: Depression, anxiety and epilepsy share some etiology factors, causing frequently observed multimodal activity of centrally active compounds. This might raise the risk of central adverse effects of potential drugs, but on the other hand ‐ in a light of common comorbidity of these diseases ‐ also make an opportunity for avoiding polypragmasy. The presented study combines rational drug design methods, chemical synthesis, receptor studies and in vivo pharmacological screening (mice, i. p.) in order to obtain new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Panczyk et al. reported the design and synthesis of a novel series of N ‐(phenoxyalkyl)‐, N ‐[2‐[2‐(phenoxy)ethoxy]ethyl]‐, or N ‐(phenoxyacetyl)piperazine derivatives having potent antidepressant‐like, anxiolytic and anticonvulsant activity [100] . The results of FST revealed that 1‐[4‐(2,5‐dimethylphenoxy)butyl]‐4‐phenethylpiperazine dihydrochloride ( 51 ) has antidepressant like activity which is lower than fluoxetine.…”
Section: Recent Advancements In Piperazine Derivatives As Antidepressantsmentioning
confidence: 99%
“…Panczyk et al. reported the design and synthesis of a novel series of N ‐(phenoxyalkyl)‐, N ‐[2‐[2‐(phenoxy)ethoxy]ethyl]‐, or N ‐(phenoxyacetyl)piperazine derivatives having potent antidepressant‐like, anxiolytic and anticonvulsant activity [100] . The results of FST revealed that 1‐[4‐(2,5‐dimethylphenoxy)butyl]‐4‐phenethylpiperazine dihydrochloride ( 51 ) has antidepressant like activity which is lower than fluoxetine.…”
Section: Recent Advancements In Piperazine Derivatives As Antidepressantsmentioning
confidence: 99%
“…Reports on the anticonvulsant activity of the cardiovascular drugs propranolol (Fischer et al, 1985;Fischer, 2002) and mexiletine (Chew et al, 1979) prompted many scientists to search for other aminoalkanol and/or aroxyalkyl derivatives possessing similar properties and functions. For the last two decades, a group of aminoalkanol and aroxyalkyl derivatives have gained much attention due to their anticonvulsant activity (Marona et al, 2005;Pę kala et al, 2011;Waszkielewicz et al, 2013Waszkielewicz et al, , 2015Waszkielewicz et al, , 2016Pań czyk et al, 2018Pań czyk et al, , 2019. Research carried out by our team involved the crystal structure analysis of the tested compounds and an analysis of their anticonvulsant activity.…”
Section: Introductionmentioning
confidence: 99%